2015
DOI: 10.1017/s204579601500013x
|View full text |Cite
|
Sign up to set email alerts
|

Does low coping efficacy mediate the association between negative life events and incident psychopathology? A prospective-longitudinal community study among adolescents and young adults

Abstract: Our findings suggest that NLE and low perceived CE elevate the risk for various incident mental disorders and that low CE partially mediates the association between NLE and incident depression. Subjects with NLE might thus profit from targeted early interventions strengthening CE to prevent the onset of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The high path coefficients of the relationship between competence/control beliefs and coping in our models suggest that both constructs represent a higher-order phenomenon known as “coping-efficacy” ( 85 ), which refers to an individual’s beliefs about the efficacy of coping in the future based on previous coping-experiences. In line with our results, coping-efficacy mediated the relationship between childhood adversities as well as trauma and depression ( 86 ) and was linked to suicidality ( 87 ).…”
Section: Discussionsupporting
confidence: 91%
“…The high path coefficients of the relationship between competence/control beliefs and coping in our models suggest that both constructs represent a higher-order phenomenon known as “coping-efficacy” ( 85 ), which refers to an individual’s beliefs about the efficacy of coping in the future based on previous coping-experiences. In line with our results, coping-efficacy mediated the relationship between childhood adversities as well as trauma and depression ( 86 ) and was linked to suicidality ( 87 ).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous finding that high self-efficacy nurses perceive that they are better capable of accomplishing tasks (Dunn et al, 2014). Prior research also supported that high self-efficacy affects how people cope with negative events (Asselmann, Wittchen, Lieb, Höfler, & Beesdo-Baum, 2016). High self-efficacy nurses are able to generate more pathways and agency thinking than low self-efficacy nurses.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, various studies have demonstrated that the impact of LEs on long-term health outcomes depends on the experience’s characteristics, e.g., experience time as well as individual protective resources [ 11 , 13 – 17 ]. Thus, Kleiman et al [ 18 ] reported optimistic subjects to be less affected by negative LEs, and Asselmann et al [ 19 ] observed that coping efficacy mediated the impact of negative LEs on mental health. Further, Brown and McGill [ 16 , 17 ] found subjects with low self-esteem to benefit less from the buffering effect of positive LEs, and Staufenbiel et al [ 11 ] reported positive LEs to moderate the association between social support and hair cortisol levels.…”
Section: Introductionmentioning
confidence: 99%